Analysis of the Effectiveness of Learning Learners in Participating in Package C Equality Education: A Case in PKBM As Salam Tanjung Batu Ogan Ilir - Dari, Silvi Wulan; Shomedran, Shomedran; Helmi, Henny (Journal of English Language and Education, 2025)
Package C equality education program is an educational program that is equivalent to the High School level. This research aims to describe the effectiveness of citizen learning in participating in package C equality education at PKBM As Salam Tanjung Batu Ogan Ilir. The type of research used is qualitative descriptive with data collection techniques through observation, interview and documentation. The research results show that learning package C at PKBM As Salam is enough. This effectiveness is supported by several important components, such as learning planning, learning goals, learning media and methods, administration, learning facilities, citizen involvement and assessment of learning outcomes. This study also found that the majority of residents studying package C at PKBM As Salam have worked and resided outside the Tanjung Batu area. This condition affects the effectiveness of learning, especially related to the involvement of learners and the use of online and offline learning methods, each of which has advantages and disadvantages for learners.